2014
DOI: 10.1177/1934578x1400901119
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS Analysis of the Essential Oil of Leucas indica from India

Abstract: The aim of the present study was to investigate and identify the essential oil constituents of Leucas indica (L.) R.Br. (Lamiaceae). The chemical composition of the hydro-distilled essential oil was obtained from the flowering aerial parts of L. indica for the first time. The oil was analyzed by gas chromatography equipped with flame ionization detector (GC-FID) and gas chromatography coupled with mass spectrometry (GC/MS). Fifty-six compounds were identified, representing 99.1% of the total oil. The main cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…The injector temperature was set at 230°C, and the injection volume was 0.1 μL in n-hexane, with a split ratio of 1:50. MS was taken at 70 eV with a mass range of m/z 40-450 [34,35]. Identification of constituents was done on the basis of retention index (RI), determined with reference to homologous series of n-alkanes C 8 -C 25 under identical experimental conditions, by comparing with the MS literature data [36] and coinjection of commercial samples from Sigma-Aldrich, India (≥ 98% purity).…”
Section: Chromatographic Analysismentioning
confidence: 99%
“…The injector temperature was set at 230°C, and the injection volume was 0.1 μL in n-hexane, with a split ratio of 1:50. MS was taken at 70 eV with a mass range of m/z 40-450 [34,35]. Identification of constituents was done on the basis of retention index (RI), determined with reference to homologous series of n-alkanes C 8 -C 25 under identical experimental conditions, by comparing with the MS literature data [36] and coinjection of commercial samples from Sigma-Aldrich, India (≥ 98% purity).…”
Section: Chromatographic Analysismentioning
confidence: 99%
“…While chemical investigation of the volatile oil of the African L. aspera detected carvone, carvacrol, and menthol as major components [ 17 ], a recent report by Joshi et al (2016) [ 18 ] on the volatile oil of the Indian L. aspera uncovered that the oil is rich in sesquiterpene hydrocarbons (47.7%), where β-caryophyllene was the fundamental constituent with a percentage of 34.2% [ 18 ]. Whereas Joshi (2014) [ 23 ] confirmed the dominance of β-caryophyllene (51.1%) in the L. indica essential oil, Vagionas et al (2007) [ 22 ] found that the fundamental chemical class in L. glabrata is oxygenated monoterpenes (64.4%), with menthone (31.8%) and pulegone (11.4%) as essential constituents. Moreover, high contents of β-cubebene (38.1%), α-pinene (19.7%), and trans-caryophyllene were detected in L. milanjiana oil [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…MS was taken at 70 eV with a mass range of m/z 40–450, and other parameters used were those reported earlier. [1617] The major constituent of the essential oil of A. glauca was identified and confirmed (co-injection of commercial sample from Sigma-Aldrich, India (≥98% purity).…”
Section: Methodsmentioning
confidence: 98%